Radiologic Approaches In The Detection And Monitoring of Multiple Pregnancy Complications - Osho ES; Ojo-Rowland OT; Bello AO; Bamidele JF; Oyun A; Fatukasi JI (BULLETIN OF OBSTETRICS AND GYNAECOLOGY, 2025)
Multiple pregnancy, defined as the gestation of two or more fetuses, is a high-risk condition asso- ciated with increased maternal and fetal morbidity and mortality. The global incidence varies geo- graphically, with Africa particularly Nigeria recording the highest rates. Twin pregnancies consti- tute over 98% of multiple gestations, and their risk profile intensifies with the number of fetuses. Complications such as preterm birth, fetal growth restriction, twin-to-twin transfusion syndrome (TTTS), and maternal hypertensive disorders are common. Radiology plays a pivotal role in the diagnosis, monitoring, and management of multiple pregnancies. Ultrasound remains the corner- stone imaging modality due to its safety, accessibility, and real-time imaging capability. It is indis- pensable in determining chorionicity, detecting congenital anomalies, and assessing fetal growth and wellbeing. Advanced modalities, including high-resolution ultrasound, 3D/4D imaging, Dop- pler, and fetal MRI, have further enhanced diagnostic accuracy, enabling early detection and guided interventions such as fetoscopic laser ablation and intrauterine transfusion. Although the use of ionizing modalities like CT and X-ray is limited due to teratogenic risks, they remain essential in maternal life-threatening emergencies. The integration of artificial intelligence (AI) into radiologic imaging promises greater precision, automation, and predictive power in future obstetric care. Keywords: Multiple Pregnancy, Twin to Twin Syndrome, Doppler, Ultrasound. References 1. Kazandi, M. and Turan, V. (2011) “Multipl Pregnancies and Their Complications,” Journal of Turkish Society of Obstetric and Gynecology, 8(1), pp. 21–24. Available at: https://doi.org/10.5505/ tjod.2011.47704. 2. Arrowsmith, S. (2023) “Multiple pregnancies, the myometrium and the role of mechanical factors in the timing of labour,” Current Research in Physiology, 6. Available at: https://doi.org/10.1016/j. crphys.2023.100105. 3. Santana, D.S., Surita, RG. and Cecatti, J.G. (2018) "Multiple pregnancy: Epidemiology and association with maternal and perinatal morbidity" Revista Brasileira de Ginecologia e Obstetricia. Georg Thieme Verlag. pp. 554-562. Available at: https://doi.org/10.1055/s-0038-1668117. 4. Omonkhua, A.A., Okonofua, EE., Ntoimo, LEC, Aruomaren, A.L., Ade- bayo, A.M. and Nwuba, R., 2020. Community perceptions on causes of high dizygotic twinning rate in Igbo-Ora, South-west Nigeria A qualitative study. PLOS ONE, 15(12), p.e0243169. https://doi. org/10.1371/journal.pone.0243169. 5. Igbodike, EP, Ijarotimi, O.A., Ubom, A.E., Eleje, G.U., God'swill, CC., Okpala, BC, Nwaogu, N.L., Ajenifuja, KO, Ikechebelu, J.L, Loto, OM, Onwudiegwu, U., Eke, AC, 2024. Trends and outcomes of twin births in Southwest Nigeria: A 14-year retrospective cohort study. Exploratory Research in Hypothesis Medicine, 9(1), pp.15-24. https://doi.org/10.14218/ERHM.2023.00039. 6. Olotu, P.N., Olotu, LA, Yakubu, N.S., Onche, E.U., Famojuro, T.I., Datok, T., et al, 2023. A review of Nigerian plants and their bioactive constituents that increase chances of multiple pregnancies. Journal of Pharmacognosy and Phytochemistry, 12(4), pp.1-4. https:// dolorg/10.22271/phyto 2023.v1214c.14685. 7. Lazarov, S., Lazarov, L. and Lazarov, N. (2016) "Complications of multiple pregnancies. Overview," Trakia Journal of Science, 14(1), pp. 108-111. Available at: https://doi.org/10.15547/tjs.2016.01.016 8. Oblechina, NJ, Okolie, V., Eleje, G, Okechukwu, Z. and Anemeje, O., 2011. Twin versus singleton pregnancies: the incidence, pregnancy complications, and obstetric outcomes in a Nigerian tertiary hospital. International Journal of Women's Health, 3, pp.227-230. https:// doLorg/10.2147/IJWHS22059 9. Ananth, C.V. and Chauhan, S.P, 2012. Epidemiology of twinning in developed countries. Seminars in Perinatology, 36(3), pp.156-161. https://doi.org/10.1053/semper.2012.02.001. 10. Matthews, TJ., MacDorman, M.F. and Thoma, M.E., 2015. Infant mortality statistics from the 2013 period linked birth/infant death data set. National Vital Statistics Reports, 64, pp.1-30. 11. National Institute for Health and Clinical Excellence, 2011. Multiple Pregnancy: The Management of Twin and Triplet Pregnancies in the Antenatal Period. [online] Available at: https://www.nice.org. uk/guidance/cg129 [Accessed 10 January 2017]. 12. Bellizzi, S., Sobel, H., Betran, A.P. and Temmerman, M., 2018. Early neonatal mortality in twin pregnancy: findings from 60 low- and middle-income countries. Journal of Global Health, 8, p.010404. 13. Roman, A., Ramirez, A. and Fox, N.S., 2022. Prevention of preterm birth in twin pregnancies. American Journal of Obstetrics & Gynecology MFM, 4, p.100551. 14. Trevett, T. and Johnson, A., 2005. Monochorionic twin pregnancies. Clinical Perinatology, 32(2), pp.475-494, vill. https://doi. org/10.1016/j.cp.2005.02.007. 15. Gyamfifi, C., Stone, J. and Eddleman, KA, 2005. Maternal complications of multifetal pregnancy. Clinical Perinatology, 32(2), pp.431-442, vii. https://doi.org/10.1016/j.clp.2005.02.004. 16. Coonrod, D.V, Hickok, D.E., Zhu, K., Easterling, TR. and Daling, J.R., 1995. Risk factors for preeclampsia in twin pregnancies: a population-based cohort study. Obstetrics & Gynecology, 85(5 Pt 1), pp. 645-650. https://doi.org/10.1016/0029-7844(95)00049-W. 17. Sibai, B.M., Hauth, J. Caritis, S, et al, 2000. Hypertensive disorders in twin versus singleton gestations. American Journal of Obstetrics and Gynecology, 182(4), pp.938-942. https://doi.org/10.1016/ S0002-9378(00)70350-4. 18. Cunningham, F.G., Leveno, K.J., Bloom, S.L., Hauth, J.C., Gilstrap, L. III and Wenstrom, K.D., 2005. Multifetal gestation. In: Cunningham, FG., Leveno, K.J., Bloom, S.L., Hauth, J.C., Gilstrap, L. III and Wenstrom, K.D. (eds.) Williams Obstetrics. 22nd ed. New York, NY: McGraw-Hill, pp. 911-948. 19. Kwan, M., Miglioretti, D., Marlow, E., Aiello Bowles, E.J., Weinmann, S.Y., Cheng, S., et al., 2019. Trends in medical imaging during pregnancy in the United States and Ontario, Canada, 1996 to 2016. JAMA Network Open, 2, p.e197249. 20. Bourgioti, C. et al. (2021) "Imaging during pregnancy: What the radiologist needs to know," Diagnostic and Interventional Imaging. Elsevier Masson s.r.l., pp. 593-603. Available at: https://doi. org/10.1016/j.diii.2021.05.003. 21. Ahn, H. (2025) "Imaging in Acute Obstetric Conditions: A Pictorial Essay," Korean Journal of Radiology, 26(5). Available at: https://doi. org/10.3348/kjr.2025.0037. 22. Tirada, N., Dreizin, D., Khati, N.J., Akin, E.A. and Zeman, R.K., 2015. Imaging pregnant and lactating patients. Radiographics, 35, pp.1751-1765. 23. Malinowski, A.K., Sen, J. and Sermer, M., 2015. Hyperreactio luteinalis: maternal and fetal effects. Journal of Obstetrics and Gynaecology Canada, 37, pp.715-723 24. Ganer Herman, H., Kogan, Z., Tairy, D., Ben Zvi, M., Kerner, R., Ginath, S., et al., 2018. Pregnancies following hysteroscopic removal of retained products of conception after delivery versus abortion. Gynecologic and Obstetric Investigation, 83, pp.586-592. 25. Yu, F.N.Y. and Leung, K.Y., 2021. Antenatal diagnosis of placenta accreta spectrum (PAS) disorders. Best Practice & Research Clinical Obstetrics & Gynaecology, 72, pp.13-24. 26. Gopireddy, D.R., Virarkar, M., Kumar, S., Vulasala, S.S.R., Nwachukwu, C. and Lamsal, S., 2022. Acute pelvic pain: a pictorial review with magnetic resonance imaging. Journal of Clinical Imaging Science, 12, p.48. 27. Mullany, K., Minneci, M., Monjazeb, R. and Coiado, O., 2023. Overview of ectopic pregnancy diagnosis, management, and innovation. Women's Health (London), 19, p.17455057231160349 28. Licci, M., Guzman, R., Soleman, J., 2019. Maternal and obstetric complications in fetal surgery for prenatal myelomeningocele repair: a systematic review. Neurosurgical Focus, 47(4), E11. 29. Corroenne, R., Yepez, M., Barth, J., et al., 2020. Chorioamniotic membrane separation following fetal myelomeningocele repair: incidence, risk factors and impact on perinatal outcome. Ultrasound in Obstetrics & Gynecology, 56(5), pp.684-693. 30. Jha, P. et al. (2021) "Role of imaging in obstetric interventions: Criteria, considerations, and complications," Radiographics, 41(4), pp. 1243-1264. Available at: https://doi.org/10.1148/ rg.2021200163. 31. Jelin, E., Hirose, S., Rand, L., et al., 2010. Perinatal outcome of conservative management versus fetal intervention for twin reversed arterial perfusion sequence with a small acardiac twin. Fetal Diagnosis and Therapy, 27(3), pp.138-141. 32. Johnson, M.P. and Wilson, R.D., 2017. Shunt-based interventions: why, how, and when to place a shunt. Seminars in Fetal & Neonatal Medicine, 22(6), pp.391-398. 33. Crystal, M.A. and Freud, L.R., 2019. Fetal aortic valvuloplasty to prevent progression to hypoplastic left heart syndrome in utero. Birth Defects Research, 111(8), pp.389-394. 34. Bamberg, C. and Hecher, K., 2019. Update on twin-to-twin transfusion syndrome. Best Practice & Research Clinical Obstetrics & Gynaecology, 58, pp.55-65. 35. Abbasi, N., Cortes, M.S., Ruano, R., et al., 2020. Bamberg, C. and Hecher, K., 2019. Update on twin-to-twin transfusion syndrome. Best Practice & Research Clinical Obstetrics & Gynaecology, 58, pp.55-65. 36. Ishan Kumar. Evolution of Obstetric Sonography. CRIJ [Internet]. 2017 Feb. 22(1):1-2. Available from: https://medwinpublisher. org/index.php/CRIJ/article/view/1736 37. Douglas A, Daniel A, Veluri S. History of the Ultrasound Machine in Obstetrics and Gynecology. Academic Medicine & Surgery. Published online March 20, 2024. doi:10.62186/001c.115458 38. Campbell S. A short history of sonography in obstetrics and gynaecology. Facts Views Vis Obgyn. 2013;5(3):213-229 39. Salomon, L. J., Alfirevic, Z., Berghella, V., et al. (2019). ISUOG practice guidelines: Ultrasound in pregnancy. Ultrasound in Obstetrics & Gynecology, 53(6), 715-723. 40. World Health Organization (WHO). (2021). WHO recommendations on antenatal care for a positive pregnancy experience. 41. Reddy, U. M., Abuhamad, A. Z., Levine, D., & Saade, G. R. (2021). Fetal imaging: Executive summary of a joint Eunice Kennedy Shriver NICHD, AIUM, and SMFM workshop. Journal of Ultrasound in Medicine, 40(6), 1103-1112. 42. Abramowicz JS, Barnett SB, Duck FA, Edmonds PD, Hynynen KH, Ziskin MC. AIUM bioeffects consensus report: Fetal thermal effects of diagnostic ultrasound. J Ultrasound Med. 2008;27(4):541-559 43. Slaghekke F., Favre R., Peeters S.H., Middeldorp J.M., Weingertner A.S., van Zwet E.W., Klumper F.J., Oepkes D., Lopriore E. Laser surgery as a management option for twin anemia-polycythemia sequence. Ultrasound Obstet. Gynecol. 2014;44:304-310. doi: 10.1002/ uog.13382 44. Hata T, Aoki S, Akiyama M, Yanagihara T, Miyazaki K. Three- dimensional ultrasonographic assessment of fetal hands and feet. Ultrasound Obstet Gynecol. 1998;12(4):235-239. 45. Honemeyer U, Talic A, Therwat A, Paulose L, Patidar R. The clinical value of KANET in studying fetal neurobehavior in normal and at- risk pregnancies. J Perinat Med. 2013;41:187-97. doi: 10.1515/jpm- 2012-0195 46. Kurjak A, Stanojević M, Salihagić-Kadić A, Spalldi Barišić L, Jakovljević M. Is Four-Dimensional (4D) Ultrasound Entering a New Field of Fetal Psychiatry? Psychiatr Danub. 2019 Jun;31(2):133-140. 47. Griffiths, P. D., Bradburn, M., Campbell, M. J., Cooper, C. L., Embleton, N., Graham, R., Hart, A. R., Jarvis, D., Kilby, M. D., Lie, M., Mason, G., Mandefield, L., Mooney, C., Pennington, R., Robson, S. C., & Wailoo, A. (2019). MRI in the diagnosis of fetal developmental brain abnormalities: The MERIDIAN diagnostic accuracy study (Health Technology Assessment, No. 23.49). NIHR Journals Library. 48. Masselli G, Cozzi D, Ceccanti S, Laghi F, Giancotti A, Brunelli R. Fetal body MRI for fetal and perinatal management. Clin Radiol. 2021 Sep;76(9):708.e1-708.e8. 49. Brugger, P.C. (2010). Methods of Fetal MRI. In: Prayer, D. (eds) Fetal MRI. Medical Radiology(). Springer, Berlin, Heidelberg. https://doi. org/10.1007/174_2010_29 50. Glen, J., Bruemmer-Smith, S., & Greenway, T. (2006). Introduction of an echocardiography service to a general intensive care unit. Anaesthesia, 61(3), 288-293 51. Giles W, Bisits A, O'Callaghan S, Gill A; DAMP Study Group. The Doppler assessment in multiple pregnancy randomised controlled trial of ultrasound biometry versus umbilical artery Doppler ultrasound and biometry in twin pregnancy. BJOG. 2003 52. Kim, E., & Boyd, B. (2022). Diagnostic imaging of pregnant women and fetuses: literature review. Bioengineering, 9(6), 236. 53. Yaseen, I., & Rather, R. A. (2024). A theoretical exploration of artificial intelligence's impact on Feto-maternal health from conception to delivery. International Journal of Women's Health, 903-915. 54. Hill, B., Skouteris, H., Boyle, J. A., Bailey, C., Walker, R., Thangaratinam, S., & Teede, H. J. (2020). Health in preconception, pregnancy and postpartum global alliance: international network pregnancy priorities for the prevention of maternal obesity and related pregnancy and long-term complications. Journal of clinical medicine, 9(3), 822. 55. Albakri, A. A., Alzahrani, M. M., Alghamdi, S. H., Albakri, A., & ALGHAMDI, S. (2024). Medical imaging in pregnancy: safety, appropriate utilization, and alternative modalities for imaging pregnant patients. Cureus, 16(2). 56. Cohoon, T. J., & Bhavnani, S. P. (2020). Toward precision health: applying artificial intelligence analytics to digital health biometric datasets. Personalized Medicine, 17(4), 307-316. 57. Dwivedi, Y. K., Hughes, L., Ismagilova, E., Aarts, G., Coombs, C., Crick, T., ... & Williams, M. D. (2021). Artificial Intelligence (AI): Multidisciplinary perspectives on emerging challenges, opportunities, and agenda for research, practice and policy. International journal of information management, 57, 101994. 58. Liu, D., Li, L., Wu, X., Zheng, D., Wang, J., Yang, L., & Zheng, C. (2020). Pregnancy and perinatal outcomes of women with coronavirus disease (COVID-19) pneumonia: a preliminary analysis. American journal of roentgenology, 215(1), 127-132. 59. Gatta, G., Di Grezia, G., Cuccurullo, V., Sardu, C., Iovino, F., Comune, R., ... & Viola, L. (2021). MRI in pregnancy and precision medicine: a review from literature. Journal of personalized medicine, 12(1), 9 60. Langdon, J. H., Chai, N., Patel, A., Steenburg, S. D., Itani, M., Katz, D. S., ... & Revzin, M. V. (2025). Imaging of trauma in pregnant patients. RadioGraphics, 45(10), e240043. 61. Chan, W. S. (2020). Can pregnancy-adapted algorithms avoid diagnostic imaging for pulmonary embolism?. Hematology 2014, the American Society of Hematology Education Program Book, 2020(1), 184-189. 62. Damilakis, J., & Papadakis, A. (2019). Radiation Dose Management of Pregnant Patients, Pregnant Staff and Paediatric Patients. IOP Publishing Limited. 63. Grufferman, S., Ruymann, F., Ognjanovic, S., Erhardt, E. B., & Maurer, H. M. (2009). Prenatal X-ray exposure and rhabdomyosarcoma in children: a report from the children's oncology group. Cancer Epidemiology Biomarkers & Prevention, 18(4), 1271-1276. 64. Demma, J. A., Cohen, L., Dior, U. P., Marom, G., Kedar, A., Cohain, N. L., & Appelbaum, L. (2023). Effect of magnetic resonance imaging on acute surgical treatment of pregnant patients: a single institution study. Israel Med Assoc J, 25, 392-7. 65. Recio Rodríguez, M., Andreu-Vázquez, C., Thuissard-Vasallo, I. J., Cano Alonso, R., Bermejo López, C., Tamarit Degenhardt, I., & Martínez Ten, P. (2020). Real-life diagnostic accuracy of MRI in prenatal diagnosis. Radiology research and practice, 2020(1), 4085349. 66. Alghamdi SA Sr. Gadolinium-Based Contrast Agents in Pregnant Women: A Literature Review of MRI Safety. Cureus. 2023 May 3;15(5):e38493. 67. Ratiu, D., Hide-Moser, K., Morgenstern, B., Gottschalk, I., Eichler, C., Ludwig, S., ... & Thangarajah, F. (2019). Doppler indices and notching assessment of uterine artery between the 19th and 22nd week of pregnancy in the prediction of pregnancy outcome. in vivo, 33(6), 2199-2204. 68. Antunes M, Viana CR, Charepe Z. Hope Aspects of the Women's Experience after Confirmation of a High-Risk Pregnancy Condition: A Systematic Scoping Review. Healthcare (Basel). 2022 Dec 8;10(12):2477. 69. Olagunju, O. J., Egbo, B., Osanyinlusi, O. O., Olagunju, O. E., Olorunmolu, S. E., Ben, E., & Olagunju, O. (2025). Assessing the role of ultrasound scanning in improving pregnancy outcomes in Potiskum and neighboring rural communities in Yobe State, Nigeria. Cureus, 17(2). 70. Smith, J., Treadwell, M. C., & Berman, D. R. (2018). Role of ultrasonography in the management of twin gestation. International Journal of Gynecology & Obstetrics, 141(3), 304-314. 71. Maruotti, G. M., Saccone, G., Morlando, M., & Martinelli, P. (2016). First-trimester ultrasound determination of chorionicity in twin gestations using the lambda sign: a systematic review and meta-analysis. European Journal of Obstetrics & Gynecology and Reproductive Biology, 202, 66-70. 72. Dewald, O., & Hoffman, J. T. (2023). Gestational Sac Evaluation. In StatPearls [Internet]. StatPearls Publishing. 73. Guedes-Martins, L., Cunha, A., Saraiva, J., Gaio, R., Macedo, F., & Almeida, H. (2014). Internal iliac and uterine arteries Doppler ultrasound in the assessment of normotensive and chronic hypertensive pregnant women. Scientific Reports, 4(1), 3785. 74. Cohen, Y., Gutvirtz, G., Avnon, T., & Sheiner, E. (2024). Chronic hypertension in pregnancy and Placenta-Mediated complications regardless of preeclampsia. Journal of Clinical Medicine, 13(4), 1111 75. Gratacós, E., Lewi, L., Munoz, B., Acosta-Rojas, R., Hernandez- Andrade, E., Martinez, J. M., ... & Deprest, J. (2007). A classification system for selective intrauterine growth restriction in monochorionic pregnancies according to umbilical artery Doppler flow in the smaller twin. Ultrasound in Obstetrics & Gynecology, 30(1), 28-34. 76. Emery, S. P., Bahtiyar, M. O., Moise, K. J., & North American Fetal Therapy Network. (2015). The North American fetal therapy network consensus statement: management of complicated monochorionic gestations. Obstetrics & Gynecology, 126(3), 575-584. 77. Mills, J. L. (1982). Malformations in infants of diabetic mothers. Teratology, 25(3), 385-394. 78. Kucera, J. (1971). Rate and type of congenital anomalies among offspring of diabetic women. J. Reprod. Med., 7, 61-70. 79. Cochrane Pregnancy and Childbirth Group, Buijtendijk, M. F., Bet, B. B., Leeflang, M. M., Shah, H., Reuvekamp, T., ... & de Bakker, B. S. (1996). Diagnostic accuracy of ultrasound screening for fetal structural abnormalities during the first and second trimester of pregnancy in low-risk and unselected populations. Cochrane Database of Systematic Reviews, 80. Rashid, S. Q. (2013). Amniotic fluid volume assessment using the single deepest pocket technique in Bangladesh. Journal of Medical Ultrasound, 21(4), 202-206.